Characterization of Brevibacillus laterosporus Cas9 (BlatCas9) for Mammalian Genome Editing - Gao, Ning; Zhang, Chengdong; Hu, Ziying; Li, Miaomiao; Wei, Jingjing; Wang, Yongming; Liu, Huihui (Frontiers in Cell and Developmental Biology, 2020)
Compact CRISPR/Cas9 systems that can be delivered by AAV for in vivo genome editing hold great promise for clinical applications. Brevibacillus Laterosporus Cas9 (BlatCas9) is a compact Cas9 nuclease that has been identified for plant genome editing. Here, we characterize BlatCas9 as an alternative tool for mammalian genome editing. We demonstrate that BlatCas9 requires a simple N4C PAM in mammalian cells. We further demonstrate that BlatCas9 enables genome editing in a variety of cell types. Importantly, BlatCas9 can be packaged into AAV for genome editing. Finally, we characterize the specificity of the BlatCas9. In summary, BlatCas9 offers an alternative tool for both basic research and clinical applications.